College van B & W achter tafel tijdens metro-debatten. Vlnr.: Van Duyn, Sinnige, Lammers, Verhey en Samkalden - Singels, Han, (1975)
College van B & W achter tafel tijdens metro-debatten. Vlnr.: Van Duyn, Sinnige, Lammers, Verhey en Samkalden.